Role of Minimally Invasive Percutaneous Nephrolithotomy Techniques-Micro and Ultra-Mini PCNL (<15F) in the Pediatric Population: A Systematic Review - Jones, Patrick; Bennett, Grace; Aboumarzouk, Omar M; Griffin, Stephen; Somani, Bhaskar K (Journal of endourology, 2017)
Management of pediatric stone disease is challenging, with standard percutaneous nephrolithotomy (PCNL) having a good stone-free rate (SFR), but with associated high complication rates. Miniaturization of this technique has led to the rise of minimally invasive PCNL techniques such as micro (<10F) and ultra-mini (<15F) PCNL procedures. Our objective was to perform a systematic review of the literature to evaluate the success and complication rates of minimally invasive PCNL techniques in the pediatric age group (<18 years). A Cochrane style search was performed and the following bibliographic databases were accessed: PubMed, Science direct, Scopus, and Web of Science. This was carried out in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. A total of 14 studies (456 patients), including 8 on micro-PCNL (m-PCNL, n = 233) and 6 on ultra-mini PCNL (UMP, n = 223), were included. Mean stone size ranged from 12-16.5 mm (m-PCNL) and 12-41 mm (UMP), and the overall SFR ranged from 80% to 100% (m-PCNL) and 85% to 100% (UMP). The overall complication rates for all studies were 11.2%, which was slightly higher for UMP (13.9%). Postoperative renal colic or fragment obstruction was only seen in m-PCNL, but there was a statistically significant rate of extravasation or renal pelvicaliceal perforation and hematuria for UMP compared with m-PCNL. Miniaturized PCNL techniques can deliver high SFRs with a small risk of Clavien I/II complications. The size of tract seems to influence the nature of complications, with higher hematuria and renal extravasation with increasing tract size.